Starry messenger : a book depicting the life of a famous scientist, mathematician, astronomer, philosopher, physicist, Galileo Galilei - d (New York : Farrar, Straus, Giroux, 1996)
Describes the life and work of Galileo who changed the way people saw the galaxy, by offering objective evidence that the earth was not the fixed center of the universe.
Wilson's Children, October 2010.
Elem. School Library Collection, June 2000.
School Library Journal starred, October 1996.
Notable/Best Books (A.L.A.), January 1997.
Book Links (A.L.A.), September 2006.
Booklist starred, October 1996.
Keywords: Galilei, Galileo, -- 1564-1642 -- Biography -- Juvenile literature; Galileo, -- 1564-1642.; Galileo, -- 1564-1642.; Astronomers -- Italy -- Biography -- Juvenile literature; Scientists -- Italy -- Biography -- Juvenile literature; Scientists; Scientists -- Biography; Astronomers -- Biography; Biographies